2012
DOI: 10.1007/s00220-012-1418-y
|View full text |Cite
|
Sign up to set email alerts
|

Effective Action and Phase Transitions in Yang-Mills Theory on Spheres

Abstract: We study the covariantly constant Savvidy-type chromomagnetic vacuum in finite-temperature Yang-Mills theory on the four-dimensional curved spacetime. Motivated by the fact that a positive spatial curvature acts as an effective gluon mass we consider the compact Euclidean spacetime S 1 × S 1 × S 2 , with the radius of the first circle determined by the temperature a 1 = (2π T ) −1 . We show that covariantly constant Yang-Mills fields on S 2 cannot be arbitrary but are rather a collection of monopole-antimonopo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…We will need the asymptotics of the function Ω(t) obtained in [11]. We have as t → 0 14) and as t → ∞,…”
Section: Jhep11(2015)193mentioning
confidence: 99%
See 1 more Smart Citation
“…We will need the asymptotics of the function Ω(t) obtained in [11]. We have as t → 0 14) and as t → ∞,…”
Section: Jhep11(2015)193mentioning
confidence: 99%
“…In [9] we applied these methods to study quantum gravity and Yang-Mills theory on any symmetric space. Further, we applied these methods to study the thermal Yang-Mills theory on product of spheres, such as S 1 × S 1 × S 2 and S 1 × S 3 in [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In four dimensions there are not many choices of spaces of non-negative constant curvature, only products of spheres and circles; the non-flat ones are S 1 × S 1 × S 2 and S 1 × S 3 . The case of S 1 × S 1 × S 2 was studied in our previous paper [11] and in this paper we studied the case of S 1 × S 3 . One of our results is the calculation of the heat kernel of the Laplacian acting on arbitrary fields on S 3 in arbitrary representation of SU (2).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent paper [11] we considered the finite temperature Yang-Mills theory on S 1 × S 1 × S 2 with an Abelian covariantly constant background on S 2 . We showed that despite the positive spatial curvature the gluon operator still has negative modes for any compact semi-simple gauge group, which means that the vacuum with covariantly constant chromomagnetic fields on S 2 does not represent the true vacuum of Yang-Mills theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation